2022
DOI: 10.3390/diagnostics12061459
|View full text |Cite
|
Sign up to set email alerts
|

Causes and Risk Factors of Pediatric Spontaneous Intracranial Hemorrhage—A Systematic Review

Abstract: Previous studies suggest that the most common cause of spontaneous intracerebral hemorrhage in children and adolescents is arteriovenous malformations (AVMs). However, an update containing recently published data on pediatric spontaneous intracranial hemorrhages is lacking. The aim of this study is to systematically analyze the published data on the etiologies and risk factors of pediatric spontaneous intracranial hemorrhage. This systematic review was performed in compliance with Preferred Reporting Items for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…A study reported that in children over 5 years of age, like the patient in the case, SICH usually occurs due to vascular malformations. Vascular malformations in children can have several risk factors, such as connective tissue disorders, fibromuscular dysplasia, and vasculitis due to infection or inflammation [1,[5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study reported that in children over 5 years of age, like the patient in the case, SICH usually occurs due to vascular malformations. Vascular malformations in children can have several risk factors, such as connective tissue disorders, fibromuscular dysplasia, and vasculitis due to infection or inflammation [1,[5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, advances in diagnosis and earlier surgical intervention have improved the prognosis of SICH itself. In addition, the brain in pediatric has good tissue plasticity and ability to repair cerebrovascular lesions [5,7].…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial haemorrhage necessitates urgent evaluation and treatment by medical professionals. Early recognition and appropriate medical intervention are vital for a positive prognosis and recovery [3]. The stacking and blending method has the ability to combine the advantages of several basic models and has proven to be greater in terms of intrusion detection, electricity consumption prediction, and daily reference evaporation [10].…”
Section: Introductionmentioning
confidence: 99%
“… 8 Although rare, intracranial hemorrhage can have devastating effects on pediatric populations. An estimated one-third of pediatric patients who experienced an ICH die, 9 and those that survive may suffer neurodevelopmental effects 10 from long-standing neurologic, cognitive, and adaptive behavior impairments affecting their potential independence and social functioning. 11 In the aforementioned study, Ishi et al found that all reported patients ( n = 4) with an FGFR1 mutation experienced spontaneous ICH at some point during their course of treatment.…”
mentioning
confidence: 99%